Analysis of Wildlife Migration Patterns and Habitat Connectivity in Malaysia - Humaira, Alya (International Journal of Environmental Sciences, 2024)
Purpose: The aim of the study was to investigate the analysis of wildlife migration patterns and habitat connectivity in Malaysia. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Recent studies on wildlife migration patterns in Malaysia highlight critical corridors for genetic diversity and species resilience, emphasizing the urgent need for conservation efforts to combat habitat fragmentation. Spatial analysis techniques have been crucial in mapping optimal routes and prioritizing conservation areas, offering valuable guidance for policymakers and conservationists aiming to sustain Malaysia's biodiversity. Unique Contribution to Theory, Practice and Policy: Met population theory, landscape ecology theory & movement ecology theory may be used to anchor future studies on the analysis of wildlife migration patterns and habitat connectivity in Malaysia. Insights from wildlife migration studies inform practical conservation strategies. Policies informed by migration research can address climate change impacts on wildlife by preserving migration corridors that allow species to adapt to changing environmental conditions.